Reclaiming Native Hawaiian Knowledge Represented in Bird Taxonomies - Gomes, Noah (Ethnobiology Letters, 2020)
This paper examines three examples of native bird classification systems historically used by the aboriginal peoples of the Hawaiian Islands. The goal is to better understand Indigenous linguistic hierarchies in the taxonomic structure and nomenclature systems that were formerly utilized by these colonized peoples. Three specific manuscripts from two native historians and a foreign naturalist are analyzed to better ascertain how these systems may have worked, despite the dearth of data on the comprehensive knowledge of bird hunters and ritual specialists. The utilitarian basis of these systems is shown to have potential practical application for the ongoing cultural and linguistic revitalization of the native Hawaiian people. The perspectives and reasoning behind these systems could be used as a tool for reviving traditional relationships with the unique ecosystems of Hawaiʻi. Further research in the large but diffuse archives of Hawaiian language manuscripts may eventually expand our understanding of Hawaiian folk systematics.